2021 IEEE World Haptics Conference (WHC) 2021
DOI: 10.1109/whc49131.2021.9517250
|View full text |Cite
|
Sign up to set email alerts
|

Alfred: the Haptic Butler On-Demand Tangibles for Object Manipulation in Virtual Reality using an ETHD

Abstract: We present "Alfred", a novel haptic paradigm for object manipulation in 3D immersive virtual reality (VR). It uses a robotic manipulator to move tangible objects in its workspace such that they match the pose of virtual objects to be interacted with. Users can then naturally touch, grasp and manipulate a virtual object while feeling congruent and realistic haptic feedback from the tangible proxy. The tangible proxies can detach from the robot, allowing natural and unconstrained manipulation in the 3D virtual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It is felt that a large number of useful applications, in manufacturing design, and design verification, are amenable to this approach with existing technology." [37] McNeely hence evokes using <virtual:physical> mappings (Figure 9): as a thorough 1:1 mapping is more complex to build, a physical object can for instance overlay multiple virtual ones [22,40]. Advances in Pseudo-Haptics 4 demonstrated that objects of approximately similar primitives can be used to simulate the same object, without altering the user's perception.…”
Section: Solutions For Mitigationmentioning
confidence: 99%
“…It is felt that a large number of useful applications, in manufacturing design, and design verification, are amenable to this approach with existing technology." [37] McNeely hence evokes using <virtual:physical> mappings (Figure 9): as a thorough 1:1 mapping is more complex to build, a physical object can for instance overlay multiple virtual ones [22,40]. Advances in Pseudo-Haptics 4 demonstrated that objects of approximately similar primitives can be used to simulate the same object, without altering the user's perception.…”
Section: Solutions For Mitigationmentioning
confidence: 99%
“…For example, Lee et al [43] developed a remote control approach to manipulate the robot end effector movement with hand gestures through virtual reality controllers. Robot arms are also widely used in encountered-type haptics to continuously follow and match the user's actions [3,22,52,72]. For example, Araujo et al [3] used a robot arm to provide feeling of textures through a tactile device on a robot arm and simple interactions through buttons.…”
Section: Encountered-type Hapticsmentioning
confidence: 99%
“…For example, Araujo et al [3] used a robot arm to provide feeling of textures through a tactile device on a robot arm and simple interactions through buttons. Mercado et al [52] used a robot arm to provide an on-demand tangible surface by placing a physical plane under the contact area when the user is putting an object on a surface in the virtual world. Such approaches have been evaluated and the results seem to indicate that they enhance immersive experiences as they provide real-time "being there" sensation when interacting with virtual objects [3,29,52].…”
Section: Encountered-type Hapticsmentioning
confidence: 99%
See 2 more Smart Citations